2013
DOI: 10.3390/toxins5071219
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Aflatoxin B1 during the Fermentation of Alcoholic Beverages

Abstract: Aflatoxin B1 (AFB1) is a contaminant of grain and fruit and has one of the highest levels of carcinogenicity of any natural toxin. AFB1 and the fungi that produce it can also contaminate the raw materials used for beer and wine manufacture, such as corn and grapes. Therefore, brewers must ensure strict monitoring to reduce the risk of contamination. In this study, the fate of AFB1 during the fermentation process was investigated using laboratory-scale bottom and top beer fermentation and wine fermentation. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…in food, including grape must, has been observed previously [12,44,68]. These fungi have the potential to produce mycotoxins, which can be dangerous if consumed in large quantities [69,70]. However, low levels of mycotoxins are common in commercial wines [70], and Canadian wines typically have a lower concentration of mycotoxins than wines produced elsewhere in the world [71].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in food, including grape must, has been observed previously [12,44,68]. These fungi have the potential to produce mycotoxins, which can be dangerous if consumed in large quantities [69,70]. However, low levels of mycotoxins are common in commercial wines [70], and Canadian wines typically have a lower concentration of mycotoxins than wines produced elsewhere in the world [71].…”
Section: Resultsmentioning
confidence: 99%
“…However, low levels of mycotoxins are common in commercial wines [70], and Canadian wines typically have a lower concentration of mycotoxins than wines produced elsewhere in the world [71]. Furthermore, the process of alcoholic fermentation has been shown to reduce the presence of mycotoxins, through enzymatic conversion to a less toxic form and/or the adsorption to lees and subsequent removal from the wine [69,72]. E. necator (also called Uncinula necator ) is a grapevine pathogen responsible for powdery mildew, and is found in all regions of the world where grapes are grown [73].…”
Section: Resultsmentioning
confidence: 99%
“…Reportedly, such processing can reduce AFB 1 by 20–30% and OTA by 20–69% but does not change the level of DON in beer . Such losses have been linked to the adsorption to yeast cells or solid particles . Reports have shown that AFB 1 , OTA and DON are not degraded by S. pastorianus (or S. cerevisiae ) during fermentation .…”
Section: Fate Of Mycotoxins During the Brewing Processmentioning
confidence: 99%
“…Such losses have been linked to the adsorption to yeast cells or solid particles . Reports have shown that AFB 1 , OTA and DON are not degraded by S. pastorianus (or S. cerevisiae ) during fermentation . The work by Johnston et al .…”
Section: Fate Of Mycotoxins During the Brewing Processmentioning
confidence: 99%
“…However, fermented beverages based on lactic acid bacteria metabolism may suffer less from mycotoxin contamination as fungal colonization is considerably more difficult, since these bacteria can produce antimicrobial substances during the malting process [93,96]. Degradation of AFB 1 has already been described during alcoholic beverage fermentation [97]. In yet another example, fermented apple juice (produced from fruit previously inoculated with Penicillium exapansum) using Saccharomyces cerevisiae exhibited lower PAT concentrations when compared to the unfermented and the pasteurized juices [98].…”
Section: Fermented Beveragesmentioning
confidence: 99%